SNAPPERGPS: Open Hardware for Energy-Efficient, Low-Cost Wildlife Location Tracking with Snapshot GNSS - Jonas Beuchert; Amanda Matthes; Alex Rogers (Journal of Open Hardware, 2023)
Location tracking with global navigation satellite systems (GNSS), such as GPS, is used in many applications, including the tracking of wild animals for research. Snapshot GNSS is a technique that only requires milliseconds of satellite signals to infer the position of a receiver. This is ideal for low-power applications such as animal tracking. However, there are few existing snapshot systems, none of which is open source. To address this, we developed SNAPPERGPS, a fully open-source, low-cost, and low-power location tracking system designed for wildlife tracking. SnapperGPS comprises three parts, all of which are open-source: (i) a small, low-cost, and low-power receiver; (ii) a web application to configure the receiver via USB; and (iii) a cloud-based platform for processing recorded data. This paper presents the hardware side of this project. The total component cost of the receiver is under $30, making it feasible for field work with restricted budgets and low recovery rates. The receiver records very short and low-resolution samples resulting in particularly low power consumption, outperforming existing systems. It can run for more than a year on a 40 mAh battery. We evaluated SNAPPERGPS in controlled static and dynamic tests in a semi-urban environment where it achieved median errors of 12 m. Additionally, SNAPPERGPS has already been deployed for two wildlife tracking studies on sea turtles and sea birds. Metadata Overview Main design files: https://github.com/SnapperGPS/snappergps-pcb Target group: biologists tracking animal movement Skills required: PCB manufacturing and assembly (can be outsourced) – advanced; Replication: this hardware has been replicated by every author. See section “Build Details” for more detail.